The Impact of Time-Restricted Eating and Intermittent Fasting on Glycemia, Body Weight, and Overall Well-Being in Patients with Type 2 Diabetes – A Review of Studies - Szymon Przemysław Stolarczyk; Kuba Borys Romańczuk; Zofia Martyna Wójcik; Bartosz Omasta; Daria Rybak; Magdalena Agata Czerska; Paulina Dorota Pietrukaniec; Olga Krupa; Katarzyna Kamińska-Omasta; Kinga Furtak (Quality in Sport)
Introduction Intermittent fasting is becoming increasingly popular, particularly among individuals with obesity. One variation of this approach is time-restricted eating (TRE), which involves consuming meals only during a specific time window, typically lasting between eight to twelve hours each day.